Phase Inversion Tissue Harmonic Sonographic Imaging: A Clinical Utility Study - Rosenthal, Stanton J; Jones, Paul H; Wetzel, Louis H (American journal of roentgenology (1976), 2001)
We evaluated the utility of phase inversion tissue harmonic sonographic imaging in a variety of clinical applications. Two hundred randomly selected patients were scanned with both fundamental and tissue harmonic methods on a sonography system. The following transducers were used: 2.5 MHz, 20 mm phased array; 3 MHz, 40 mm curved array; 6.5 MHz, 13 mm curved array transvaginal; and 7.5 MHz, 40 mm linear. Operators evaluated visualization of normal and pathologic tissues by tissue harmonic versus fundamental imaging using scores ranging from 1 for much worse visualization to 5 for much better visualization. They also assessed the overall utility of tissue harmonic imaging in the diagnosis of the patient's condition. The studies were saved on magnetooptical disc and were independently reviewed by one of the authors. Tissue harmonic imaging was helpful for all types of examination. Tissue harmonic imaging improved visualization of normal tissue in 49% of the cases and pathologic tissue in 73% of the cases. Tissue harmonic imaging was found to be diagnostically helpful in 43% of the cases and essential to the diagnosis in 6% of the cases. Tissue harmonic imaging significantly improves visualization of both normal and pathologic tissues and its selective use has major diagnostic utility in a wide variety of clinical applications.